STRATEGIC VIGILANCE AND ITS IMPACT ON ENHANCING ADAPTIVE PERFORMANCE A SURVEY OF THE OPINIONS OF A SAMPLE OF OFFICERS IN THE WASIT GOVERNORATE POLICE DIRECTORATE - Dr. Ammar Abdel Amir Zwain; Ali Talib Abd Daham (European Journal of Humanities and Educational Advancements, 2022)
This study aims to investigate the relationship between strategic vigilance and adaptive performance, specifically in the Wasit Governorate Police Directorate, despite the scarcity of studies that attempted to determine the nature of the relationship between the study variables (strategic vigilance, adaptive performance). The organizational environment of any organization is "lack of interest in enhancing adaptive performance in light of a low level of strategic vigilance". This study gained its importance as it sheds light on two important variables at the organizational and functional level in organizations, namely (strategic vigilance and adaptive performance(. In this study, electronic questionnaire technology was used to collect data. The researcher focused on the officers working in the Wasit Governorate Police Directorate as the target study community (236), and the final number of participants in the study was (218), i.e. a response rate of (92,37%). Where several statistical techniques were employed for statistical analysis by the two programs SPSS and Smart-PLS, and the study came out with the following: Theoretical results: There is a knowledge gap to explain the nature of the relationship between the study variables (strategic vigilance and adaptive performance) in organizations in general and security institutions in particular. Process: The practical results showed an influence relationship between the study variables, which is a direct influence relationship between strategic vigilance and adaptive performance.